The influence of service quality on the loyalty of Telekom's Customer / Intan Syalia Wahid - Wahid, Intan Syalia (Faculty of Business and Management, 2011)
The aim of this research was to understand the relationship between service quality and customer loyalty. The significance of this research is intended to help Telekom Malaysia Berhad to establish the service offered and identified what are the important aspects of service quality in keeping the customer loyalty. All questionnaires were base on walk in interview and customer loyalty system that is distributed randomly. 175 samples were collected from different branch of Telekom in Kuantan. Cronbach’s Alpha test was carried out to test the reliability of each construct. Then Paired t-test test was carried out to compare the elements of service quality with customer loyalty to see whether or not there are significance difference between customer loyalty and service quality elements. Regressions Test was used to test the most important element of service quality on Customer Loyalty based on customer perception. In addition to that, Hierarchical Regression Model test was used to test the relationship between the most important element of service quality and customer loyalty. Overall findings from this study suggest there were significant relationship in between Service Quality and Customer Loyalty. The findings also suggest that there were another element that needs to be considering instead of the elements of Service Quality. In conclusion, the results suggest Telekom Malaysia Berhad to focus more effort in improving their service quality especially on the aspect of empathy. Based on the test result, empathy has proven to be the most important dimension in customer loyalty. Because of the limitation of the resources, the study’s scope has limited to study particularly in the areas of service quality offered by Telekom Malaysia Berhad with the absence of technical quality. Therefore the study might not reflect the technical quality or functional quality that JKR Malaysia has also offered which might also influence the customer loyalty in other context.